Impact of classroom management on student performance in secondary schools - Usharani Khuntia; Prakash Kumar Sahoo (Journal of Education, Social & Communication Studies, 2025)
In secondary education environments, student performance outcomes depend much on good classroom management. The relationship between several classroom management techniques and their observable impacts on academic performance, engagement, and socioemotional development among teenage students is investigated in this work. Studies of the present literature show that well-organized management strategies—especially those stressing clear standards, consistent routines, and good teacher-student relationships—correlate considerably with better academic performance across subject areas. Furthermore indicated by the studies are learning environments where students feel less anxious, more motivated, and more in control thanks to effective management strategies. Particularly secondary schools using focused classroom management training courses for teachers note notable increases in attendance rates, standardized exam results, and drop in disciplinary events. These findings underline the vital role of classroom management as not only a tool for behavioral control, but as a fundamental pedagogical framework that directly effects educational outcomes and student achievement in secondary education situations.